Enhanced and secured hybrid steganography model for hiding large data - Majumder, Srabony; Tanu, Mohon Dash; Faisal, S. M. Fahim; Sristy, Mumtahinah Rahman; Paul, Rigan (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.